Implementasi Papan Statistika (PATIA) Untuk Meningkatkan Hasil Belajar Mean, Modus, Median Dan Kuartil Data Tunggal Siswa Kelas VIII di SMP Negeri 1 Jombang - Silvia Lailatunnissa; Farit Dwi Ratnasari; Jauhara Dian Nurul Iffah; Nurwiani Nurwiani; Syarifatul Maf’ulah (Jurnal Pengabdian Masyarakat, 2025)
This community service is motivated by the problems experienced by the partners. The partner of this community service is SMP Negeri 1 Jombang. The problems in question are: (1) Students have difficulty understanding statics material, especially in finding the mean, mode, median and quartile of single data. (2) Statistics board learning media (PATIA) has never been applied to statistics material, especially to find the mean, mode, median and quartile of single data. Therefore, the solution that will be implemented by the community service team as a form of community service is to apply PATIA learning media as an effort to strengthen conceptual understanding of statistics material, especially to find the mean, mode, median and quartile of single data for class VIII students at SMP Negeri 1 Jombang. Learning media is a learning media used to convey information related to statistics material, especially to find the mean, mode, median and quartile of single data. PATIA learning media is expected to help make it easier for students to abstract and understand statistics material. The implementation method involves three stages: preparation, implementation, and evaluation. The results of this community service are that the PATIA learning media can strengthen conceptual understanding of statistics materials, especially in finding the mean, mode, median, and quartiles of single data. This community service activity has a positive impact on teachers and students through the use of PATIA learning media in the classroom. Teachers' skills in implementing PATIA learning media and student learning motivation have increased, and this community service activity helps teachers deliver material in a practical and easy-to-understand manner.